Myodesopsia is a symptom of central nervous system blast crisis in chronic myeloid leukemia. (2019) - Ishii, Kazuyoshi; Nakaya, Aya; Fujita, Shinya; Satake, Atsushi; Azuma, Yoshiko; Tsubokura, Yukie; Saito, Ryo; Konishi, Akiko; Hotta, Masaaki; Yoshimura, Hideaki; Ito, Tomoki; Nomura, Shosaku
Highlights : Patient with chronic myeloid leukemia in the chronic phase developed myodesopsia. Patient was in molecular response in bone marrow. It was an isolated central nervous system blast crisis. Abstract: A 49-year-old woman diagnosed with chronic myeloid leukemia in the chronic phase was started on dasatinib treatment, after which she complained of myodesopsia. Nineteen months after diagnosis, the patient again complained of myodesopsia and developed bilateral optic neuritis. Cerebrospinal fluid analysis revealed an increase in blasts, although peripheral blood and bone marrow examination confirmed that the patient remained in a molecular response to tyrosine kinase inhibitor (TKI) therapy. The patient was diagnosed with an isolated central nervous system blast crisis, a rare occurrence with second-generation TKI therapy, and the initial presentation of myodesopsia represented a symptom of this condition.